Factorial Invariance of an Integrated Measure of Classroom Sense of Community in Face-to-Face and Online Courses. (December 2014) - Cho, YoonJung; Hathcoat, John D.; Bridges, Stacey L.; Mathew, Susan; Bang, Hyeyoung
The aim of the present study was to develop a more integrated measure of classroom sense of community (SOC) while testing factorial invariance of the measurement structure across face-to-face and online courses. We incorporated two existing SOC measures to capture both context-specific and context-general characteristics of SOC and developed an integrated scale of classroom SOC with a four-factor structure. Tests of measurement invariance indicated that the new measure of classroom SOC has equivalent patterns of factor loadings, strength of factor loadings, and intercepts across the two course delivery modes, thus making this a viable measure to examine potential differences across these contexts. Latent mean analysis indicated that students in an online course perceived a lower level of SOC.